Perturbation distribution coefficient definition - Kulahci, Fatih; Sen, Zekai (Parlar Scientific Publications (P S P), 2008)
In general, the classical distribution coefficient (K-D) is defined as the ratio of the element concentration in the sediment to that of the same element in water. The definition implies a ratio rather than a distribution, which requires a set of data for its validity. Although it is possible to calculate the value of K-D at a set of given sites individually, provided that deep sediment and water concentrations are available, one cannot make spatial deductions about the regional features of the same concentrations. Besides, each concentration includes uncertainties, even though it is measured in the field or laboratory. In order to account for the spatial behavior of the concentrations, calculated K-D values are treated with perturbation method, which is applied to find the regional average population character of K-D. It is proven that not only averages, but also variances and the correlation coefficient of the concentrations, play significant roles in the spatial distribution of the K-D values. The application of the methodology is presented for Cs-137 element in Keban Dam reservoir, Turkey, through 40 sampling sites that are irregularly scattered in the reservoir.
Keywords: distribution coefficient; spatial distribution; perturbation method; lake; cesium